Fully-discrete finite element approximation for a family of degenerate parabolic problems - Acevedo, Ramiro; Gómez, Christian; López-Rodríguez, Bibiana (Mathematical Modelling and Analysis, 2022)
The aim of this work is to show an abstract framework to analyze the numerical approximation by using a finite element method in space and a BackwardEuler scheme in time of a family of degenerate parabolic problems. We deduce sufficient conditions to ensure that the fully-discrete problem has a unique solution and to prove quasi-optimal error estimates for the approximation. Finally, we show a degenerate parabolic problem which arises from electromagnetic applications and deduce its well-posedness and convergence by using the developed abstract theory, including numerical tests to illustrate the performance of the method and confirm the theoretical results.